Understanding the effect of wet etching on damage resistance of surface scratches - Benoit Da Costa Fernandes (Nature Portfolio, 2018)
Abstract Fused silica optics often exhibit surface scratches after polishing that radically reduce their damage resistance at the wavelength of 351 nm in the nanosecond regime. Consequently, chemical treatments after polishing are often used to increase the damage threshold and ensure a safe operation of these optics in large fusion-scale laser facilities. Here, we investigate the reasons for such an improvement. We study the effect of an HF-based wet etching on scratch morphology and propose a simple analytic model to reflect scratch widening during etching. We also use a finite element model to evaluate the effect of the morphological modification induced by etching on the electric field distribution in the vicinity of the scratch. We evidence that this improvement of the scratch damage resistance is due to a reduction of the electric field enhancement. This conclusion is supported by secondary electron microscopy (SEM) imaging of damage sites initiated on scratches after chemical treatment.